The ECRG4 cleavage product augurin binds the endotoxin receptor and influences the innate immune response during otitis media - Kurabi, Arwa; Hur, Dong Gu; Pak, Kwang; Gibson, Madeline; Webster, Nicholas J. G.; Baird, Andrew; Eliceiri, Brian P.; Ryan, Allen F. (Frontiers in Genetics, 2022)
Otitis media (OM), the most common disease of childhood, is typically characterized by bacterial infection of the middle (ME). Prominent features of OM include hyperplasia of the ME mucosa, which transforms from a monolayer of simple squamous epithelium with minimal stroma into a full-thickness respiratory epithelium in 2-3 days after infection. Analysis of the murine ME transcriptome during OM showed downregulation of the tumor suppressor gene Ecrg4 that was temporally related to mucosal hyperplasia, and identified stromal cells as the primary ECRG4 source. The reduction in Ecrg4 gene expression coincided with cleavage of ECRG4 protein to release an extracellular fragment, augurin. The duration of mucosal hyperplasia during OM was greater in Ecrg4-/- mice, the number of infiltrating macrophages was enhanced and ME infection cleared more rapidly. ECRG4-null macrophages showed increased bacterial phagocytosis. Co-immunoprecipitation identified association of augurin with TLR4, CD14 and MD2, the components of the lipopolysaccharide (LPS) receptor. The results suggest that full-length ECRG4 is a sentinel molecule that potentially inhibits growth of the ME stroma. Processing of ECRG4 protein during inflammation, coupled with a decline in Ecrg4 gene expression, also influences the behavior of cells that do not express the gene: limiting the production of growth factors by epithelial and endothelial cells, as well as the activity of macrophages.